European welfare state constitutions after the financial crisis - Becker, Ulrich; Poulou, Anastasia, 1988- (Oxford : Oxford University Press, 2020)
This text examines the specific reforms in social protection that took place during the European financial crisis, while embedding them in a broader human rights and constitutional law framework of nine European countries. Analytical and comprehensive, this is a helpful tool for all legal professionals that deal with crisis-related reforms.
This edition also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 4, 2020).
Keywords: Public welfare -- Law and legislation -- European Union countries -- History -- 21st century; Welfare state -- European Union countries -- History -- 21st century; Constitutional law -- European Union countries -- History -- 21st century